Disseminated coccidioidomycosis in a patient with juvenile idiopathic arthritis receiving infliximab - Megan Trainor (Pediatric Rheumatology Online Journal, 2021)
Abstract Background Coccidioides immitis is a dimorphic fungus endemic to the arid climates of the Southwest United States, Mexico and parts of Central and South America. Human infection occurs through inhalation of spores with less than half of exposures progressing to a symptomatic state that primarily consists of pulmonary manifestations. Disseminated coccidioidomycosis is exceedingly rare, occurring in fewer than 1 % of symptomatic infections. Through hematogenous spread, the fungus can infect most organ systems and may be fatal without systemic antifungal treatment. Individuals with impaired cell-mediated immunity either from primary immunodeficiency disorders or secondary to immunosuppression with medications such as tumor necrosis factor alpha (TNF-α) inhibitors have increased risk of disseminated coccidioidomycosis and previous cases of coccidioidomycosis have been reported with biologic therapy. Case presentation We present a case of disseminated coccidioidomycosis in a 16-year-old female with polyarticular juvenile idiopathic arthritis (JIA) being treated with prednisone, methotrexate, and infliximab. The patient presented with symptoms of meningeal irritation, bilateral choroidal lesions, and necrotizing peripheral pneumonia. Her infection was thought to be a reactivation of coccidioidomycosis given her history of resolved pneumonia that occurred after traveling to Arizona, New Mexico, and El Paso one year prior to presentation. Following diagnosis, she improved with discontinuation of her immunosuppressive medications and two weeks of intravenous amphotericin B and fluconazole with plans for lifetime treatment with fluconazole while immunosuppressed. Due to worsening arthritis, she will begin tofacitinib and continue close monitoring of chest x-rays and coccidioides antibody. Conclusions Patients undergoing immunosuppressive therapy for rheumatological conditions are at increased risk of disseminated coccidioidomycosis and should be evaluated with high suspicion when presenting with atypical symptoms and history of travel to endemic regions.